PENGETAHUAN TENTANG PEMELIHARAAN KESEHATAN GIGI DAN DESKRIPSI JUMLAH KARIES GIGI IBU PEKERJA DI KELURAHAN TUALANG KECAMATAN PERBAUNGAN SERDANG BEDAGAI - Herlinawati, Herlinawati (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2018)
Dental caries can be deffined as a dental tissue disease characterized by tissue damage, starting from thetooth surface. Knowledge is the result of knowing a particular object through one’s sense. A working motheris defined as a mother doing an activity outside herhouse. The purpose of this study was to find out thedescription of knowledge of working mother about dental and oral health care towards the happening ofdental caries in Tualang Village Perbaungan Serdang Bedagai District. The research was a descriptivestudy with survey method. All of the population, 50 working mothers,were taken as samples of the research.Mother's knowledge data about dental and oral health care werecollected from questionnaires, distributed toall samples, while the dental caries data werecollectedthrough direct dental and mouth examination. Basedon the research, the levels of the respondents knowledge about dental and oral health care were as thefollowing : 20 respondents (40%) were in good category, 14 respondents (28%) were in medium categorywhile 16 respondents (32%) were in the poor category. A number of 50 respondents had dental cariesamounted to 302, an average of 6.04, with a percentage of 100%. It is expected that the working mothersable to improve their knowledge and behavior maitain dental and oral health care, so it can be applied tofamily member since oral and dental health will influence body health